Predecessors’ Attitude toward Conflict Predictor of Family Business Sustainability - Linda Salim; Mohd. Noor Shariff; Darwina Ahmad Arshad (Faculty of Business, President University, 2018)
Using qualitative interviews to understand the mindset of family business leaders in succession, this study proposes that attitude toward conflict is an important decision making element. A collective case studies uncover how attitude toward conflict predicts decision making during succession and influence optimism on the future of the firms. Findings of the study suggest that predecessors who welcome conflicts as a part of family firms take a more relaxed attitude toward succession, with a wider talent pool. This group are also more egalitarian in strategic decision making and optimistic toward the future of the firms. Predecessors who avoid conflict have smaller talent pool, making decisions to nominate few for the position. They is cautious, making decisions for the successors, and are pessimistic about the future of the firms. Contributions from this study are threefold. First, we introduce the use of attitude toward conflict to measure predecessors' behaviors during succession. Second, through identification of attitude toward conflict, we contribute to the literature by predicting predecessors' optimisms toward the future of the firms in the hands of the next generations. Third, this study contributes another dimension to reciprocal nepotism through discovery that family businesses upholding reciprocal nepotism behave differently.